The Edinburgh critical history of nineteenth-century philosophy - Stone, Alison, 1972- (Edinburgh critical history of philosophy., 2011)
This volume begins with the rise of German Idealism and Romanticism, traces the developments of naturalism, positivism, and materialism and of later-century attempts to combine idealist and naturalist modes of thought. Written by a team of leading international scholars this crucial period of philosophy is examined from the novel perspective of themes and lines of thought which cut across authors, disciplines, and national boundaries. This fresh approach will open up new ways for specialists and students to conceptualise the history of 19th-century thought within philosophy, politics, religious studies and literature.